Acute dietary nitrate supplementation does not attenuate oxidative stress or the hemodynamic response during submaximal exercise in hypobaric hypoxia - Carriker, C. R.; Rombach, P.; Stevens, B. M.; Vaughan, R. A.; Gibson, A. L. (Applied Physiology, Nutrition, and Metabolism, 2018)
The purpose of this study was to investigate changes in oxidative stress, arterial oxygen saturation (SaO2), blood pressure (BP), and heart rate (HR) during exercise in hypobaric hypoxia following acute dietary nitrate supplementation. Nine well-trained (maximal oxygen consumption, 60.8 ± 7.8 mL/kg·min) males (age, 29 ± 7 years) visited the laboratory on 3 occasions, each separated by 1 week. Visit 1 included a maximal aerobic cycling test and five 5-min increasing-intensity exercise bouts in a normobaric environment (1600 m). A single dose of either a nitrate-depleted placebo (PL) or a nitrate-rich beverage (NR; 12.8 mmol nitrate) was consumed 2.5 h prior to exercise during visits 2 and 3 (3500 m) in a double-blind, placebo-controlled, crossover study consisting of a 5-min cycling warm-up and 4 bouts, each 5 min in duration, separated by 4-min periods of passive rest. Exercise wattages were determined during visit 1 and corresponded to 25%, 40%, 50%, 60%, and 70% of normobaric maximal oxygen consumption. Catalase and 8-isoprostane were measured before and after exercise (immediately before and 1 h postexercise, respectively). NR increased plasma nitrite (1.53 ± 0.83 µmol/L) compared with PL (0.88 ± 0.56 µmol/L) (p < 0.05). In both conditions, postexercise (3500 m) 8-isoprostane (PL, 23.49 ± 3.38 to 60.90 ± 14.95 pg/mL; NR, 23.23 ± 4.12 to 52.11 ± 19.76 pg/mL) and catalase (PL, 63.89 ± 25.69 to 128.15 ± 41.80 mmol/min·mL; NR, 78.89 ± 30.95 to 109.96 ± 35.05 mmol/min·mL) were elevated compared with baseline resting values (p < 0.05). However, both 8-isoprostane and catalase were similar in the 2 groups (PL and NR) (p = 0.217 and p = 0.080, respectively). We concluded that an acute, pre-exercise dose of dietary nitrate yielded no beneficial changes in oxidative stress, SaO2, BP, or HR in healthy, aerobically fit men exercising at 3500 m.